Radio Luhak Nan Tuo FM: Dari UPT Ke Lembaga Penyiaran Publik Lokal (LPPL) di Tanah Datar (2004-2018) - Anisa Yulia; Hendra Naldi (Jurnal Kronologi, 2019)
This research is to determine the history and development of Luhak Nan Tuo FM radioin Tanah Datar District, in a context that is focused on changing the status from UPTto LPPL. This research is important because Luhak Nan Tuo FM radio a role as a centerfor disseminating local information in Tanah Datar District. The method used is ahistorical method which consists of four stages namely heuristics, source criticism,interpretation and historiography. The results of this study see the development of LuhakNan Tuo FM radio which is divided into three periods,that is: First, the beginning ofthe birth of Luhak Nan Tuo FM radio which emerged due to the absence of specialmedia between the goverment and the community in Tanah Datar District. Secondly, theinitial development of Luhak Nan Tuo FM radio (2004-2008) with the status of theTechnical Implementation Unit. Thirdly, the development of programs and technicalbroadcasting of Luhak Nan Tuo radio (2008-2018) with the status of Local PublicBroadcasting Intitutions.